Identifying Student Subgroups as a Function of School Level Attributes: A Multilevel Latent Class Analysis - Sideridis, Georgios D.; Tsaousis, Ioannis; Al-Harbi, Khaleel (Frontiers in Psychology, 2021)
The purpose of the present study was to profile high school students’ achievement as a function of their demographic characteristics, parent attributes (e.g., education), and school behaviors (e.g., number of absences). Students were nested within schools in the Saudi Arabia Kingdom. Out of a large sample of 500k, participants involved 3 random samples of 2,000 students measured during the years 2016, 2017, and 2018. Students were nested within 50 high schools. We adopted the multilevel latent profile analysis protocol put forth by Schmiege, Masyn, and Bryan (2018) and Makikangas et al (2018) that account for nested data and tested latent class structure invariance over time. Results pointed to the presence of a 4-profile solution based on BIC, the Bayes factor, and several information criteria put forth by Masyn (2013). Latent profile separation was mostly guided by parents’ education and the number of student absences (being positive and negative predictors of high achievement classes, respectively). Two models tested whether the proportions of level 1 profiles to level 2 units are variable and whether level 2 profiles vary as a function of level 1 profiles. Results pointed to the presence of significant variability due to schools.